Diffusion of H in Zircaloy-2 and Zr-2.5%Nb rolled plates between 250 °C and 350 °C by off-situ neutron imaging experiments - Santisteban, Javier Roberto; Buitrago Montañez, Nayibe Lucia; Moya Riffo, Alvaro Esteban; Soria, Sergio Raul; Baruj, Alberto Leonardo; Schulz, M.; Grosse, M.; Luzin, V.; Hache, M.; Barrow, L.; Daymond, M. R. (Elsevier Science, 2022)
Fil: Santisteban, Javier Roberto. Comisión Nacional de Energía Atómica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina